PENDAMPINGAN PENGELOLAAN SDM INKLUSIF UNTUK MENINGKATKAN KINERJA BISNIS HOMESTAY DI DESA WISATA BANTARAGUNG - Nining Purwaningsih; Andi Kusuma Negara; Lena Erdawati; Yanthi Meitry Gunawan; Metha Dwi Apriyanti (JURNAL ABDIMAS PLJ, 2026)
The development of inclusive-based tourism villages is a crucial strategy in sustainable local economic development. Bantaragung Tourism Village has great potential in the homestay accommodation sector, but its management still faces challenges related to limited capacity and inclusive Human Resources (HR) governance—particularly the involvement of vulnerable groups, women, and local youth. This Community Service/Research aims to assist homestay owners and managers in Bantaragung Tourism Village in implementing inclusive HR management to boost their business performance. The method used is Asset-Based Community Development (ABCD) through a series of stages including socialization, excellent service training (hospitality), fair work division workshops, and direct mentoring (on-site mentoring). The results of the mentoring show an average increase in the capacity of understanding inclusive HR management of 83.3% related to the importance of inclusivity in operational services. The implementation of inclusive HR has been proven to optimize role division, improve guest service standards, and foster an adaptive work environment. This positive impact leads to an increase in homestay business performance, as indicated by a 50% Understanding of the Concept of Inclusivity and positive reviews from tourists. The success of this program confirms that inclusive human resource management is not just a social responsibility, but a strategic business strategy that can increase the competitiveness of accommodation in tourist villages.